Akulturasi Psikologis Mahasiswa Indonesia di Thailand (Studi Fenomenologi pada Peserta KKN-PPL Terpadu IAIN Tulungagung - Sa'diyah, Khalimatus; Marwing, Arman (Psikoislamika: Jurnal Psikologi Islam, 2016)
This study aims to understand the psychological acculturation dynamics of participant of KKN-PPL integrated programme in Thailand through identifying and understanding the motivation of participants to participate on KKN-PPL integrated programme in Thailand. How did Barrier as stressor which they face it, what coping strategies was used by participants, and how did the psychological acculturation process of participants in Thailand. This study is a qualitative research with phenomenological approach. the results of this research is there are basic needs such as need to have fun, need to love and belonging and need to power which are realized through their participation on the KKN- PPL integrated programme in Thailand. As for this research found that stressor was different among participants. Subjects who face initial stressor without advance stressor tend to using coping strategies focused on the problem consistenly and coping strategies centered emotions simultaneously without adaptation switching otherwise subjects who face the advance stressors tend to being decreased in pattern or transition coping strategies gradually. Furthermore, the psychological acculturation process of participant of KKN-PPL integrated programme in Thailand are the result of interaction of complex factors which affect participants to be success or failure to be integrated self or to be new self identity.